Glycan Positioning Impacts HIV-1 Env Glycan-Shield Density, Function, and Recognition by Antibodies - Wei, Qing; Hargett, Audra A; Knoppova, Barbora; Duverger, Alexandra; Rawi, Reda; Shen, Chen-Hsiang; Farney, S Katie; Hall, Stacy; Brown, Rhubell; Keele, Brandon F; Heath, Sonya L; Saag, Michael S; et al. (iScience, 2020)
HIV-1 envelope (Env) N-glycosylation impact virus-cell entry and immune evasion. How each glycan interacts to shape the Env-protein-sugar complex and affects Env function is not well understood. Here, analysis of two Env variants from the same donor, with differing functional characteristics and N-glycosylation-site composition, revealed that changes to key N-glycosylation sites affected the Env structure at distant locations and had a ripple effect on Env-wide glycan processing, virus infectivity, antibody recognition, and virus neutralization. Specifically, the N262 glycan, although not in the CD4-binding site, modulated Env binding to the CD4 receptor, affected Env recognition by several glycan-dependent neutralizing antibodies, and altered site-specific glycosylation heterogeneity, with, for example, N448 displaying limited glycan processing. Molecular-dynamic simulations visualized differences in glycan density and how specific oligosaccharide positions can move to compensate for a glycan loss. This study demonstrates how changes in individual glycans can alter molecular dynamics, processing, and function of the Env-glycan shield.
Keywords: Virology; Microbiology; Glycobiology; Biochemistry; Biological Sciences